The Influence Of Digital Marketing And Advertising On Customer Satisfaction With Price As A Moderating Variable (Case Study Of Online Shopping At Shopee - Hilton; Marudut Sianturi; Salman Faris (TRIGIN PUBLISHER, 2022)
This study aims to determine and analyze the influence of digital marketing and advertising on customer satisfaction with price as a moderating variable which is motivated by the development of the era and technology in the digital world through social media. Fraud, the number of sellers, advertisements that do not match the facts, and prices that do not match the quality are the main factors for the decline in customer satisfaction at Shopee. The theory used in this research is the theories of Marketing Management, which are related to digital marketing, advertising, customer satisfaction and price. The research method used by the researcher is a quantitative approach. Methods of data collection is done by online questionnaires and documentation studies. The analytical method used is SEM-PLS, coefficient of determination (R2), hypothesis testing (P values), and analysis of moderating variables (effect size). The population used is Shopee e-commerce users who are domiciled in Medan and the number of samples is 100 respondents using accidental sampling. The results show that digital marketing and advertising have an effect on customer satisfaction and can be moderated by price although it is not significant with a coefficient of determination of 0.573 which indicates that digital marketing and advertising have an effect on customer satisfaction which is moderated by price with a percentage level of 57.3% while the rest 42.7% is another factor that is not studied. Based on the overall results of the study, it can be concluded that digital marketing and advertising have an effect on customer satisfaction which can be moderated by price.